Chickenpox pneumonia. Case presentation. Dora Ngiza hospital, Port Elizabeth, South Africa. - Gilberto Serrano Ocaña; Juan Carlos Ortiz Sablon; Ilen Ochoa Tamayo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Chickenpox is an exanthematic highly infectious disease produced by the Varicella zoster virus (VZV), commonly occurs in childhood, 90% of cases occurred in children under 12 years of age, 10% of the population over 15 years is susceptible to suffer it. It is an airborne illness, the inhale virus cause an infection in the initial respiratory epithelium, the virus spreads to distant cells of the reticuloendothelial system, finally, there is a state of viremia with skin lesions, although the spread can also be extended to the viscera. The deterioration of the cell-mediated immunity caused by coexisting diseases, HIV infection, cancer, hemato-oncology illnesses, steroid use, as well as advanced age, smoking, chronic obstructive pulmonary disease and hemorrhagic nature of the Skin lesions, are risk factors for developing Varicella-Zoster pneumonia. In this article we describe a case of chickenpox in a young HIV positive patient complicated with Varicella-Zoster pneumonia. Despite of the treatment with acyclovir, prednisone and supportive measures had a fatal outcome.